Chile : 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Selected Issues paper discusses measures taken by the Chilean government to record moderate economic growth in 2012. The easing of fiscal stance and tightening of expenditure have proved to prevent a decline in the economy. The authorities have estimated retaining a favorable economic environment to mitigate financial risks. Banks have been asked to maintain high levels of liquidity and capital to meet expansion needs. The Executive Board has commended Chilean authorities' efforts for macrofinancial stability and management of funds.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet